The Presbyteral Council: an institution of episcopal -presbyteral communion and participation in the eparchial governance - Poothavelithara, Varghese (Dharmaram canonical studies, 2020)
This book on the presbyteral council represents a praiseworthy crowning of the specialization in Oriental Canon Law, brilliantly concluded in 2010 by the author in the Pontifical Oriental Institute, Rome. With this research study, Dr. Varghese Poothavelithara participates in the search for understanding the insights of the teachings of the Second Vatican Council in the area of the relationship between the orders of episcopate and presbyterate and its institutional manifestation in the aparchial/diocesan level through the canonical body of the presbyteral council.